Women Leaders and their Leadership Styles - Sumeshni Govender; Professor Sithabile Ntombela; Siphelele S. Makhubu (Pandian Journal of Women's Studies)
Gender inequality is a reality across the globe as women often experience marginalization of all kinds. It is in this regard that Sustainable Development Goal #5 speaks to the promotion of gender equality and empowerment of women, which is regarded as a human rights issue (United Nations, 2015). Although South Africa has made significant strides in addressing gender inequality, especially in government departments and political parties, women remain under-represented in other sectors. For example, 68% of senior leadership positions in public and private sectors are controlled by men. Worldwide, several programmes have been initiated in an attempt to address gender gaps in education, health and political representation. Hence, this article undergoes a study on the facets of women leaders and their styles in emanating their leadership.